NASM essentials of sports performance training - Clark, Micheal; Sutton, Brian G.; Lucett, Scott (Jones & Bartlett Learning, 2015)
"This text teaches future sports performance coaches and other trainers how to strategically design strength and conditioning programs to train athletes safely and effectively. You will learn NASM's systematic approach to program design with sports performance program guidelines and variables; protocols for building stabilization, strength, and power programs; and innovative approaches to speed, agility and quickness drills"--Provided by publisher.